Wasiat untuk Ahli Waris: Kritik Ekstern dan Intern Autentisitas Hadis-hadis Iarangan Wasiat untuk Ahli Waris - Sugiri, Asep (Al-Jamiah: Journal of Islamic Studies, 2004)
As one of the Islamic sources of law, hadith is always confronted with two challenges: reinterpretation and origination. Either of these two will appear any time the teaching it contents considered fail adjusting to social need and change. This holds true, for instance, in the matter of bequest to an heir. As is well-known, Islamic law of inheritance prescribes two restrictions upon bequest: first, a bequest may not exceed one-third of the estate and second, a bequest may not be made in favour of an heir. However, modern Muslim personal law, like in Egypt and Sudan, shows the contrary especially to the second restriction. Muslims of these two countries may legally make a bequest to whom he will, whether heirs or non-heirs. This directly runs counter to the hadith: "la waá¹£iyyah li-wÄrith" (no bequest to an heir). But the reforrners argue that the hadith is poorly attested. David S. Powers even suggest that the hadith is a false one. The hadith scientific approach Proposed in this article to the hadiths, as shown in al-kutub at-tisah, proved to corroborates the argument, albeit differs slightly with Powers suggestion.